Determination of Mono-crystalline Silicon Photovoltaic Module Parameters Using Three Different Methods (Journal of Engineering, 2016)
For modeling a photovoltaic module, it is necessary to calculate the basic parameters which control the current-voltage characteristic curves, that is not provided by the manufacturer. Generally, for mono crystalline silicon module, the shunt resistance is generally high, and it is neglected in this model. In this study, three methods are presented for four parameters model. Explicit simplified method based on an analytical solution, slope method based on manufacturer data, and iterative method based on a numerical resolution. The results obtained for these methods were compared with experimental measured data. The iterative method was more accurate than the other two methods but more complexity. The average deviation of the iterative method  not more than 5% of current- voltage values with the corresponding experimental data. The average deviation for the other two method 9.3% for slope method and 7.9% for simplifies method.